Visual field defect due to Hydroxychloroquine in systemic lupus erythematosus - Hossny, Elham M; Abdel Latif, Mona K; Radwan, Nesrine M; Gah Al-Rassoul, Rou’ya A (QJM : An International Journal of Medicine, 2021)
Abstract Background Hydroxychloroquine (HCQ) is used in the management of a variety of autoimmune disorders, with well-established role in dermatology and rheumatology. However, Hydroxychloroquine and chloroquine (CQ) have been associated with irreversible visual loss due to retinal toxicity. Aim of the Work screening for field affection resulting from HCQ therapy in patients with SLE and assessing the diagnostic accuracy of the investigational methods employed. Subjects and Methods This is a cross-sectional controlled study that was carried out on 90 subjects (<18 years old). It included 45 physician diagnosed SLE patients taking HCQ for more than 1 year. A 45 age-matched healthy subjects were enrolled as a control group. Visual field assessment was performed by Central 10-2 visual field testing using automated Humphery perimetry. Results In comparison to the normal field in the control group, 13 out of 45 (29%) of the patients treated with HCQ had visual field defects most commonly in the central/paracentral area in-spite of no complaint. Conclusion HCQ can affect the visual field and this was not related to the cumulative dose of the drug. Regular field assessment should be done for patients on regular HCQ treatment.